2013
DOI: 10.3109/02713683.2013.834940
|View full text |Cite
|
Sign up to set email alerts
|

What is the Effect of Pseudoexfoliation Syndrome on Renal Function in Patients without Glaucoma?

Abstract: This study showed that pseudoexfoliation syndrome does not affect biochemical and ultrasonographic parameters associated with renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In the same cohort, no association of PEX with the 30-year all-cause mortality was found [70 && ]. Conversely, several case-control studies have reported association of PEX with specific systemic diseases, such as renal artery stenosis and abdominal aorta aneurysm with the use of Doppler ultrasonography [71] (in the same cohort no association with impaired renal function was reported) [72], or coronary artery ectasia by the means of coronary angiography [73], or with lower peak systolic velocities by myocardial tissue Doppler imaging or with increased carotid intima-media thickness by carotid ultrasound measurements [74]. A recent meta-analysis tried to combine the existing data on the association of PEX with vascular diseases and included 16 eligible studies (8533 PEX cases and 135 720 controls) [75].…”
Section: Association Of Pseudoexfoliation With Systemic Diseasesmentioning
confidence: 85%
“…In the same cohort, no association of PEX with the 30-year all-cause mortality was found [70 && ]. Conversely, several case-control studies have reported association of PEX with specific systemic diseases, such as renal artery stenosis and abdominal aorta aneurysm with the use of Doppler ultrasonography [71] (in the same cohort no association with impaired renal function was reported) [72], or coronary artery ectasia by the means of coronary angiography [73], or with lower peak systolic velocities by myocardial tissue Doppler imaging or with increased carotid intima-media thickness by carotid ultrasound measurements [74]. A recent meta-analysis tried to combine the existing data on the association of PEX with vascular diseases and included 16 eligible studies (8533 PEX cases and 135 720 controls) [75].…”
Section: Association Of Pseudoexfoliation With Systemic Diseasesmentioning
confidence: 85%
“…Lower levels of BUN mean lower production in the liver or higher excretion from the kidneys. Gonen et al [36] reported that renal functions were not affected in PEX. Additionally, they did not find any differences in the urea of patients with PEX [36].…”
Section: Discussionmentioning
confidence: 99%
“…Gonen et al [36] reported that renal functions were not affected in PEX. Additionally, they did not find any differences in the urea of patients with PEX [36]. One of the limitations of this study is the limited study population.…”
Section: Discussionmentioning
confidence: 99%
“…In another cross-sectional study, 200 the prevalence of CKD was higher in controls (11.7%, n = 94) than in PEX (3.5%, n = 86, P = 0.05) and POAG (3.3%, n = 91, P = 0.049), but this difference could be attributed to a higher prevalence of diabetes mellitus in the control group; the significance disappeared after adjusting for diabetes mellitus and age, using multivariable analysis. In a prospective, case-control study, 62 the biochemical (serum creatinine, urea, blood urea nitrogen, creatinine clearance, and microalbumin) and ultrasonographic (kidney volume, resistive index and pulsatility index) parameters indicative for CKD did not differ between PEX patients (n = 49) and controls (n = 42). In a population-based cross-sectional study assessing the prevalence of PEX and its associations in a Russian population (n = 5,451), there was no association between PEX and CKD.…”
Section: Chronic Kidney Disease and Pseudoexfoliation Syndromementioning
confidence: 96%